Longitudinal relationships among depressive symptoms and three types of memory self-report in cognitively intact older adults. (16th June 2020) - Hill, Nikki L.; Mogle, Jacqueline; Bhargava, Sakshi; Bell, Tyler Reed; Bhang, Iris; Katz, Mindy; Sliwinski, Martin J.
ABSTRACT: Objectives: The current study examined whether self-reported memory problems among cognitively intact older adults changed concurrently with, preceded, or followed depressive symptoms over time. Design: Data were collected annually via in-person comprehensive medical and neuropsychological examinations as part of the Einstein Aging Study. Setting: Community-dwelling older adults in an urban, multi-ethnic area of New York City were interviewed. Participants: The current study included a total of 1, 162 older adults ( M age = 77.65, SD = 5.03, 63.39% female; 74.12% White). Data were utilized from up to 11 annual waves per participant. Measurements: Multilevel modeling tested concurrent and lagged associations between three types of memory self-report (frequency of memory problems, perceived one-year decline, and perceived ten-year decline) and depressive symptoms. Results: Results showed that self-reported frequency of memory problems covaried with depressive symptoms only in participants who were older at baseline. Changes in perceived one-year and ten-year memory decline were related to changes in depressive symptoms across all ages. Depressive symptoms increased the likelihood of perceived ten-year memory decline the next year; however, perceived ten-year memory decline did not predict future depressive symptoms. Additionally, no significant temporal relationship was observed between depressive symptoms and self-reported frequency of memory problems or perceived one-year memory decline. Conclusion: Our findings highlight the importance of testing the unique associations of different types of self-reported memory problems with depressive symptoms.